HEARING LOSS PATIENTS` TREATMENT APPROACHES, MENTAL HEALTH ISSUES, AND SOCIAL ORAL PATHOLOGIES- PART 1 - Lucian Stefan Burlea; Liana Aminov; Magda Cuciureanu; Silvia Teslaru; Sorina Mihaela Solomon; Ovidiu Stamatin; Tudor Hamburda; Carina Ana Maria Balcoș; Laurian Frâncu; Laura Elisabeta Checheriță (Romanian Society of Oral Rehabilitation, 2023)
Hearing loss (HL) is the third most prevalent chronic health problem among older adults and is quite common in our study group research. Aim of the study: This study wants to illustrate the research on the connection between HL and depression as well as the therapeutic ramifications for diagnosing and treating comorbid like intraoral rehabilitation, HL, and mental disorders also. Material and methods: The evaluated study sample was represented by 28 patients with HL, aged between 50 and 65 years old, from the Prosthodontic Clinic at "Mihail Kogalniceanu", Iasi, whose presented for treatment of TMDs in association with prosthetic treatment. Results: Most patients were with minor Grade 1 so Grade 2 (moderate), hearing depreciation with audiogram exam that it is considered obvious but tolerable, interfering with daily activities, and patients actively seek therapy. Conclusions: The treatment of patients taken in study has demonstrated a recovery through complex oral rehabilitation that certainly requires time present dedication and interest, in favour of the final patient to obtain a homeostasis at the level of the stomatogenous system and adjacent to it.